2022
DOI: 10.1007/s12567-022-00438-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic space debris removal: conceptual design of bio-inspired active debris removal scenarios

Abstract: The ever-increasing number of man-made space debris creates the need for new technologies to mitigate it. Therefore, within the ESA-funded project BIOINSPACED, biologically inspired solutions for active debris removal were investigated, conceptualized and integrated to innovative and comprehensive scenarios. In the following, the collection process of existing and new biomimetic concepts as well as the evaluation of ten concepts based on a feasibility analysis will be presented. Out of the ten, the three most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Collected ideas were assessed to identify the most promising ones, that were then integrated into holistic mission scenarios. As the last step, one of Frontiers in Space Technologies frontiersin.org these scenarios was selected for a low-tech implementation in the form of a simple demonstrator depicted in Figure 8, underlining the benefits and variety of applications for bio-inspired technical solutions for space debris removal (Banken et al, 2021(Banken et al, , 2022.…”
Section: The Bioinspaced Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Collected ideas were assessed to identify the most promising ones, that were then integrated into holistic mission scenarios. As the last step, one of Frontiers in Space Technologies frontiersin.org these scenarios was selected for a low-tech implementation in the form of a simple demonstrator depicted in Figure 8, underlining the benefits and variety of applications for bio-inspired technical solutions for space debris removal (Banken et al, 2021(Banken et al, , 2022.…”
Section: The Bioinspaced Projectmentioning
confidence: 99%
“…Nevertheless, many of the previously specified bio-inspired concepts applicable to space debris removal can also be beneficial for servicing and repair activities. Contactless containment of a small satellite based on the example of a mouth or Venus flytrap (Shahinpoor, 2011;Banken et al, 2022), for example, would allow safe repairs and maintenance without the risk of spare parts, tools and spacecraft appendages to escape as additionally generated space debris. The Venus flytrap has already been used as an inspiration for advances in the fields of robotics (Shahinpoor, 2011;Falk et al, 2022;Tauber et al, 2022).…”
Section: Servicing Manufacture and Assembly In Spacementioning
confidence: 99%
“…Therefore, reliable and affordable systems for space debris removal are essential to guarantee safe and sustainable access to Earth's orbits. [ 5 ] And capturing small‐scale space debris may become a key space mission in the future. Existing capture methods include contact and noncontact capture, [ 6 ] where contact capture has been validated in real space.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth studies of these biological capture mechanisms have promoted the design of robots. [5,17] For example, as an insectivorous plant, the Venus flytrap can be closed rapidly and then locked using tip bristles. Experiments have demonstrated that during the capture process, the flytrap leaf can complete approximately 60% of its total displacement within approximately 100 ms, which is closely related to its bistable structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation